Analisis Manajemen Risiko Pada UMKM Rental Motor Bandung Menggunakan Framework ISO 31000 dan Matriks Risiko Manajemen - Anggi Mahmudin; Yesi Amelia; Tini Kartini; Alfiana Alfiana (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to analyze the implementation of risk management in micro, small, and medium enterprises (MSMEs) in the motorcycle rental sector in Bandung using the ISO 31000 Framework and the Risk Management Matrix. The research method used is a qualitative descriptive approach with data collection techniques through interviews and observations on several MSME motorcycle rental actors. The analysis is carried out based on the stages of ISO 31000, namely context determination, risk identification, risk analysis, risk evaluation, and risk management. The results of the study indicate that the main risks faced by MSME motorcycle rentals include operational risks such as vehicle loss, late payments, and unit damage, as well as external risks such as regulatory changes and economic conditions. Based on the risk matrix, most risks are in the medium to high category, which requires mitigation strategies through improving security systems, implementing stricter rental agreements, and using vehicle tracking technology (GPS). This study is expected to be a reference for MSME motorcycle rental actors in developing an effective risk management system to improve business sustainability..